Extraction and Characterization of Natural Coagulant Made from Banana Plant Stems (Musa acuminate) for the Removal of Turbidity from Wastewater - Getachew Semegn Tiruneh; Wondalem Misganaw Golie; Fasil Alemayehu Hailu; Assefa Melaku Endris; Getahun Demeke (International Journal of Polymer Science)
Wastewater treatment with chemical coagulants has a variety of drawbacks, including sludge management, cost, concerns for human health, and environmental pollution. In light of this, a study was conducted to determine whether banana plant stem (Musa acuminate) made coagulant can effectively reduce turbidity (NTU) of wastewater. In this study, conventional extraction method was used to extract the coagulant from the banana plant stem by using NaCl (0.1, 0.5, 1 M) solvent. After extraction, the coagulation efficiency of each produced coagulant was computed in terms of their turbidity removal efficiency (%) from sampled wastewater. The sampled wastewater had an average turbidity value of 893 NTU. Response surface methodology (RSM) and central composite design (CCD) were used to study the effects of NaCl solvent concentration (M), extraction time (min), and particle size (mm) on the coagulation efficiency (%) of the extracted coagulant. In addition, the coagulant was characterized such as FTIR analysis, point of zero charge value determination, and inulin compound presence analysis. From all prepared coagulants, the maximum coagulation efficiency obtained was 86.3% at the optimum conditions, such as 0.55 M (NaCl) of solvent concentration, 1.25 mm particle size, and 20 min of extraction time. The characterized coagulant had 6.2 points of zero charge value and also had various types of functional groups. Based on the findings of this study, it can be said that the coagulant prepared from banana stems (Musa acuminate) was an efficient natural coagulant that could be applied to treat wastewater.